Verrucous hemangioma and histopathological differential diagnosis with angiokeratoma circumscriptum neviforme - Kenselyn Oppermann; Ana Letícia Boff; Renan Rangel Bonamigo (Sociedade Brasileira de Dermatologia, 2018)
Abstract: Verrucous hemangioma is a rare vascular skin disorder with an immune profile similar to vascular neoplasms, but with behavior and evolution of vascular malformations. Its main differential diagnosis is angiokeratoma circumscriptum neviforme, with an almost indistinguishable clinical presentation because both diseases appear as erythematous patches that evolve to violaceous plaques, becoming scaly and even verrucous, most commonly affecting the lower limbs. Histopathology is crucial for the correct diagnosis: while in angiokeratoma the vascular alterations are limited to the papillary dermis, verrucous hemangioma extends deep into the dermis, reaching the subcutaneous tissue.